2021
DOI: 10.1007/s00267-020-01408-z
|View full text |Cite
|
Sign up to set email alerts
|

What is Policy Analytics? An Exploration of 5 Years of Environmental Management Applications

Abstract: Our digital age is characterized by both a generalized access to data and an increased call for participation of the public and other stakeholders and communities in policy design and decision-making. This context raises new challenges for political decision-makers and analysts in providing these actors with new means and moral duties for decision support, including in the area of environmental policy. The concept of "policy analytics" was introduced in 2013 as an attempt to develop a framework, tools, and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
5
0
2
Order By: Relevance
“…The use of data analytics in the context of policy-making has also been referred to as 'policy analytics' by some authors [14]. It has been suggested that policy analytics include data-driven tools that respond to a policy need and use a transparent development process [15]. Examples of policy analytics techniques are statistics, simulations, data mining, machine learning, social network and geographic info [16].…”
Section: Harnessing Digital Technologies For Public Health Policy-makingmentioning
confidence: 99%
“…The use of data analytics in the context of policy-making has also been referred to as 'policy analytics' by some authors [14]. It has been suggested that policy analytics include data-driven tools that respond to a policy need and use a transparent development process [15]. Examples of policy analytics techniques are statistics, simulations, data mining, machine learning, social network and geographic info [16].…”
Section: Harnessing Digital Technologies For Public Health Policy-makingmentioning
confidence: 99%
“…Many fields such as environmental and public health care sciences seek to engage citizens, including laypeople, in complex decision-making processes [e.g., [1][2][3]. How to best engage citizens in complex public decision-making is still unclear, but relying on information and communication technology appears to offer substantial promise [4,5].…”
Section: General Motivationmentioning
confidence: 99%
“…La présente contribution cherche à se placer dans un espace que ces différentes approches laissent de côté. Il s'agit de mettre l'analyse de l'expertise au service des tâches qui sont assignées aux experts eux-mêmes, dans une posture performative, au sens précisé par Meinard et al (2021), tout en maintenant l'exigence critique qui est la raison d'être et l'apport distinctif des sciences humaines 5 . Sur le plan méthodologique, il s'agit donc d'allier la finesse descriptive d'une recherche participante (Platt, 1983), qui consiste en une « immersion totale dans le terrain » (Soulé, 2007) permettant aux chercheurs de « vivre la réalité des sujets qu'ils observent » (Touret et al, 2019), et l'ambition de s'inscrire dans une visée d'amélioration de l'expertise et des projets qu'elle sert.…”
Section: Yves Meinardunclassified